Latin American Society of Ethnobiology’s Code of Ethics - Committee, SOLAE Ethics; Medinaceli, Armando; Cano, Eréndira J.; Argueta, Arturo; Sanabria, Olga Lucia (Ethnobiology Letters, 2018)
Latin American Society of Ethnobiology’s Code of Ethics